Improved design of a DC-DC converter in residential solar photovoltaic system - Mantas Darameičikas; Firdaus Muhammad Sukki; Siti Hawa Abu Bakar; Nazmi Sellami; Nurul Aini Bani; Mohd Nabil Muhtazaruddin; Abdullahi Abubakar Mas’ud; Jorge Alfredo Ardila Rey (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
With growing demand in renewable energy, solar photovoltaic (PV) technology is becoming more popular. A number of research has been carried out to increase the efficiency of the PV system. One of them is improving the Switch Mode Power Supplies (SMPS) performance to ensure maximum solar energy extraction. This paper looks at buck type SMPS suitability for use in solar PV installed in residential houses. The main issues that affect the response from the output are identified. The work will utilise the LT SPICE software to carry out the simulation. The primary objective of the study is to design an improved converter controller which is more robust and is able to maintain constant output. The emphasis is on good efficiency, stability and low output voltage ripple. This could be achieved by using the current mode control (CMC) techniques – an alternative design to the voltage mode control technique (VMC). Results obtained via simulations reveal strong evidence of CMC superiority over the VMC.